Dependence of the Frequency of the Kilohertz Quasi-periodic Oscillationson X-Ray Count Rate and Colors in 4U 1608–52 - Méndez, Mariano R. (1999)
We present new results based on observations carried out with the Rossi X-ray Timing Explorer during the decay of an outburst of the low-mass X-ray binary (LMXB) and atoll source 4U 1608-52. Our results appear to resolve, at least in 4U 1608-52, one of the long-standing issues about the phenomenology of the kilohertz quasi-periodic oscillations (kHz QPOs), namely the lack of a unique relation between the frequency of the kHz QPOs and the X-ray flux. We show that despite its complex dependence on the X-ray flux, the frequency of the kHz QPOs is monotonically related to the position of the source in the color-color diagram. Our findings strengthen the idea that, as in the case of Z sources, in the atoll sources the X-ray flux is not a good indicator of and that the observed changes in the frequency of the kHz QPOs in LMXBs are driven by changes in . These results raise some concern about the recently reported detection of the orbital frequency at the innermost stable orbit in 4U 1820-30.